Foundations for Forecasting: Defining Baseline Seismicity at Fuego Volcano, Guatemala - Brill, Kyle A.; Waite, Gregory P.; Chigna, Gustavo (Frontiers in Earth Science, 2018)
Accurate volcanic eruption forecasting is especially challenging at open vent volcanoes with persistent low levels of activity and relatively sparse permanent monitoring networks. We present a description of seismicity observed at Fuego volcano in Guatemala during January of 2012, a period representative of low-level, open-vent dynamics typical of the current eruptive period. We use this time to establish a baseline of activity from which to build more accurate forecasts. Seismicity consists of both harmonic and non-harmonic tremor, rockfalls, and a variety of signals associated with frequent small eruptions. In addition, there are many small discrete events not necessarily linked to eruptions that we examine in detail here. Using arrival times recorded on a temporary, nine-station network on the edifice of Fuego, we compute a 1-D velocity model and use it to locate earthquakes. The discrete events include 5 families of repeating events. This type of description can act as a template for establishing monitoring efforts at under-studied volcanoes around the world.